Impact of Antepartum Anemia on the Development of Chorioamnionitis at Term - Archabald, Karen; Lopes, Vrishali; Anderson, Brenna (American Journal of Perinatology, 2015)
Objective The aim of this study is to assess the association of antepartum anemia with chorioamnionitis at term.Study Design This is a case control study of women with and without chorioamnionitis who delivered following spontaneous or induced labor at ≥ 37 weeks' gestation. Cases had both intrapartum fever ≥ 38°C and histologic chorioamnionitis. Controls were afebrile and matched by physician practice group. Anemia was defined by CDC guidelines as hemoglobin < 10.5 g/dL (second trimester) or < 11.0 g/dL (third trimester).Results A total of 101 cases and 197 controls were identified. The prevalence of anemia at the second and third trimester complete blood count (CBC) was significantly higher in the chorioamnionitis group (p = 0.02). This association persisted after multiple logistic regression controlling for known clinical risk factors (adjusted odds ratios, 2.47; range, 1.24–4.94).Conclusion Anemia at the time of the second and third trimester CBC was more prevalent among women who developed chorioamnionitis at term. Antepartum anemia may be a modifiable risk factor in the prevention of chorioamnionitis at term.
Keywords: anemia; chorioamnionitis; term; infection